Hubungan Tingkat Ansietas dengan Kejadian Tension-Type Headache pada Mahasiswa Rumpun Teknik Fakultas Sains dan Teknik Universitas Nusa Cendana - Theodora Pentakostin Sose Lewerang; Herman Pieter Louis Wungouw; Insani Fitrahulil Jannah; Nicholas Edwin Handoyo (Lembaga Pengembangan Kinerja Dosen, 2026)
Tension-Type Headache (TTH) is the most common type of primary headache and is often associated with psychological conditions, particularly anxiety. Engineering students represent a vulnerable population due to high academic demands, stress, and lifestyle factors. This community service activity aimed to increase awareness, knowledge, and early detection of the relationship between anxiety levels and the occurrence of TTH among Engineering students of the Faculty of Science and Engineering, Universitas Nusa Cendana. The activity was implemented through health education sessions, anxiety screening using the Zung Self-Rating Anxiety Scale (SAS), and TTH screening using the Headache Screening Questionnaire (HSQ). A total of 72 Engineering students from the 2022–2024 cohorts participated in the program through proportionate stratified random sampling. The results showed a high prevalence of anxiety (83.3%), predominantly mild to moderate anxiety, and a high prevalence of TTH (66.7%). The screening results indicated a positive tendency between anxiety levels and the occurrence of TTH. This community service activity enhanced students’ understanding of mental health, stress management, and headache prevention. The program is expected to support the development of promotive and preventive mental health initiatives for university students, particularly within engineering education settings.